Pembelajaran Seni Musik dan Lirik Lagu Dalam Upaya Peningkatan Vocabulary Berbahasa Inggris - Fitri Maisarah (Jurnal Sitakara, 2023)
Vocabularies or vocabulary is also known as one of the important things that must be understood to learn the language being studied. In this case, as it is also called, without understanding vocabulary, it will make it difficult for us to learn, especially language lessons. As one of the efforts that can be done is to introduce English learning, especially vocabulary through the technique of understanding songs. Aside from being a learning medium, songs are also an alternative that can be used by teachers to make learning more enjoyable. Songs and chants have a high level of effectiveness that can be used in introducing English vocabulary to children. The purpose of this study is as a form of attracting students' interest to increase English vocabulary among students as well as improve memory and understand vocabulary effectively. By learning songs can also help to develop pronunciation skills with good intonation in learning techniques. Children as learners will prefer this way of learning because the atmosphere is more fun and not bored. The tones contained in the song will create a happy mood. Make the child comfortable and start lulled by the tone and language conveyed. Learning vocabulary using songs is a fast way to learn English that will make children feel happy and want to learn more. From the results of community service that has been carried out, in the art of music, especially songs, it has a fairly high effectiveness that can be used in learning English vocabulary learning introduction to children according to their capacity. Keywords: Learning, Art Music, English